EFL Students’ Experience in a Language Immersion Program: A Diary Study - Daffani Nur Rohman; Entusiastik; Sri Wulandari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study will seek to find out the effectiveness of the immersive English environment in the Bidan Dormitory in developing the language and speaking confidence of EFL learners. In this research study, qualitative data collection methods were employed through diary entries of the students, observation, and interviews with the camp supervisor. The results of the study showed that continuous exposure to English, peer interaction, and structured activities facilitated linguistic proficiency and confidence. At first, the students were battling with fear, embarrassment, and a limited vocabulary due to the strict English-only rule; however, their skills improved significantly through consistent practice supported by operant conditioning principles of rewards and penalties. According to Vygotsky's Social Constructivism Theory, peer interaction and supportive community created a collaborative learning atmosphere, while some structured activities such as Morning Class and Camp Night Party aligned with Long's Interaction Hypothesis, offering active participation opportunities despite additional support needs for lower-achieving students. This immersive environment integrates the behaviorist, interactionist, and constructivist approaches to language learning so well that it highlights a number of tailored interventions, such as study clubs and personalized mentoring, that may be required to support less confident learners. The paper also confirms the potential of an immersive setting in second language acquisition and recommends that future research investigate how such settings might respond to the diverse needs of learners.